(3eNJUQ JbQjQ GdbhGYOs - (3CHh YHO Gddg eMeO GdebOSi GdMfHdis; (3GHf QLH , YHO GdQMef Hf CMeO Hf QLH GdSdGej GdHZOGOj, Rjf GdOjf CHh GdaQL,J (B795 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfg deG cGf cTa GdeSGFd ef cJGH JbQjQ GdbhGYO hJMQjQ GdahGFO hefGSHI HYVgG dG Ydi JQJjH CUd GdcJGH hPdc jSgd GdcTa efg s
(3BNQgG (B:s
(3GdMGOjI hGdYTQhf (B: (3GdUabI GdhGMOI gd JJUQa ? hbO Je hced s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai E e (B1 / 315s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs